SISTEM INFORMASI MONITORING PERKULIAHAN FAKULTAS TEKNIK BERBASIS WEB - Dako, Amirudin Y; Ilham, Jumiati; Latief, Mukhlisulfatih (Sainstek, 2013)
The study "web based of information system of lectures monitoring at Engineering Faculty " is intended to present lectures at the Faculty of Engineering activities are up to date and real time web based. The results of this study is expected to be a source of information for beneficiaries of education services either directly or indirectly. The information presented contains the activity classes held in each department in the Faculty of Engineering, State University of Gorontalo, which can be accessed via the internet browser and displayed through the big display in the lobby of the faculty. This study was made with the prototype method that allows sustainable development of information systems made by adjusting the needs and the latest in presentation technology and information systems within the framework supporting the management and development of Gorontalo State University as a university-based information technology (Information Technology / IT). From this research has developed a database called 'simpul' and web based of information system of lectures monitoring at Engineering Faculty, named 'simpul' that provides information information lectures at the Faculty of Engineering activities presented either through the internet browser and displayed in large displays that are placed in the lobby Faculty of Engineering, State University of Gorontalo.